2022
DOI: 10.1007/s00181-021-02168-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of commodity price volatility on fiscal balance and the role of real interest rate

Abstract: The objective of this study is to explore the impact of commodity price volatility on the governments’ fiscal balance. Using a dynamic panel data model for 108 countries from 1993 to 2018, this study finds that governments’ fiscal balance deteriorates with commodity price volatility, especially for commodity-exporting economies. A one standard deviation increase in commodity price volatility leads to a reduction of approximately 0.04 units in the fiscal balance as a percentage of gross domestic product. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…Regarding the objective of this study and following Medina (2021), Majumder, Raghavan and Vespignani (2022), and García-Albán, González-Astudillo and Vera-Avellán (2021), we modified the equation ( 1) by adding the CPV as an explanatory variable follows:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the objective of this study and following Medina (2021), Majumder, Raghavan and Vespignani (2022), and García-Albán, González-Astudillo and Vera-Avellán (2021), we modified the equation ( 1) by adding the CPV as an explanatory variable follows:…”
Section: Methodsmentioning
confidence: 99%
“…However, another axis of the empirical literature supports the idea that the link between CPV and tax revenue mobilization also depends on the economic policies adopted. Thus, Majumder, Raghavan and Vespignani (2022) investigated the relationship between the volatility of CPV and the budget balance within a sample of 108 developing countries (including SSA countries) over the period 1993–2018. Using a dynamic panel model, the study showed that CPV deteriorates the overall budget balance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The consumption of crude oil has increased manifolds over the years and the consumption plateau may not be achieved in the next five to ten years (Geopolitical Intelligence Services 2022; Reuters 2021; International Energy Agency (IEA) 2021). Consequently, the movement of global oil prices has a notable impact on inflation (Liu et al 2022;Kpodar and Liu 2022), the exchange rate (Wang et al 2022), and the fiscal balance of the economies (Eregha et al 2022;Majumder et al 2022). According to the estimate of the World Bank, a 10% increase in oil price has the effect of increasing consumer price inflation (CPI) in the band of 0.2-0.6% and 0.8% in the wholesale price index (WPI) in South Asian Economies (World Bank 2022a).…”
Section: Introductionmentioning
confidence: 99%